Reference Standards for Stretched Penile Length in Indian Boys - Prativa Choudhury; Shivani Phugat; Vivek Verma; Vishesh Jain; Devendra Kumar Yadav; Anjan Kumar Dhua; Sandeep Agarwala; Neeta Kumar; Prabudh Goel (Journal of Indian Association of Pediatric Surgeons)
Introduction: Stretched penile length (SPL) is a vital anthropometric measurement for providing diagnostic, therapeutic, and prognostic information. SPL variations can indicate congenital anomalies or systemic disorders and are influenced by genetic, ethnic, and environmental factors. Despite its clinical importance, comprehensive age-stratified reference data for SPL in Indian children are lacking. Objective: The objective is to systematically compile and analyse the existing data on SPL in Indian children providing reference values and centile curves in children to improve clinical assessment, diagnostic accuracy and healthcare outcomes. Materials and Methods: The evidence-synthesis was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines. Data from six eligible studies (2,221 participants aged 28 weeks–16 years) representing different parts of the country were pooled to calculate the combined mean and standard deviation. Reference values and centile curves (5th, 10th, 25th, 50th, 75th, 90th, 95th) were generated using R software. Results: The data were collected using consistent methodologies across studies, though with minor differences in measurement techniques and age stratification. The SPL is shown to increase in a non-linear fashion with the age of the participant with distinct growth patterns during infancy, childhood, and puberty. Two “isomeric” nomograms were developed due to overlapping age groups in the data. Notable growth was observed at ages 1–4, slower growth from 4 to 10 years and a pubertal growth spurt was witnessed thereafter. Wide variability in SPL was observed between ages 5 and 9 years. Conclusions: The study provides new, population-specific reference standards and centile curves for SPL in Indian children, aiding in the clinical assessment and diagnosis of genital development disorders.